Non-invasive diagnosis of Pneumocystis jirovecii pneumonia: a systematic review and meta-analysis. (January 2022) - Senécal, Julien; Smyth, Elizabeth; Del Corpo, Olivier; Hsu, Jimmy M.; Amar-Zifkin, Alexandre; Bergeron, Amy; Cheng, Matthew P.; Butler-Laporte, Guillaume; McDonald, Emily G.; Lee, Todd C.
Abstract: Background: Pneumocystis jirovecii pneumonia (PCP) is an opportunistic infection commonly affecting immunocompromised people. Diagnosis usually requires invasive techniques to obtain respiratory specimens. Minimally invasive detection tests have been proposed, but their operating characteristics are poorly described. Objectives: To systematically review and meta-analyse the performance of minimally invasive PCP detection tests to inform diagnostic algorithms. Data sources: Medline, Embase, Cochrane Library (inception to 15 October 2020). Study eligibility criteria: Studies of minimally invasive PCP detection tests were included if they contained a minimum of ten PCP cases. Participants: Adults at risk of PCP. Tests: Non-invasive PCP detection tests. Reference standard: Diagnosis using the combination of clinical and radiographical features with invasive sampling. Assessment of risk bias: Using the QUADAS-2 tool. Methods: We used bivariate and, when necessary, univariate analysis models to estimate diagnostic test sensitivity and specificity. Results: Fifty-two studies were included; most studies (40) comprised exclusively human immunodeficiency virus (HIV) -infected individuals; nine were mixed (HIV and non-HIV), two were non-HIV and one study did not report HIV status. Sampling sites included induced sputum, nasopharyngeal aspirate, oral wash and blood. The four testing modalities evaluated were cytological staining, fluorescent antibody, PCR and lactate dehydrogenase. Induced sputum had the most data available; this modality was both highly sensitive at 99% (95% CI 51%–100%) and specific at 96% (95% CI 88%–99%). Induced sputum cytological staining had moderate sensitivity at 50% (95% CI 39%–61%) and high specificity at 100% (95% CI 100%–100%), as did fluorescent antibody testing with sensitivity 74% (95% CI 62%–87%) and specificity 100% (95% CI 91%–100%). Conclusion: There are several promising minimally invasive PCP diagnostic tests available, some of which may reduce the need for invasive respiratory sampling. Understanding the operating characteristics of these tests can augment current diagnostic strategies and help establish a more confident clinical diagnosis of PCP. Further studies in non-HIV infected populations are needed.